Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Both Spencer and Jeremiah are correct in their approaches to solving the equation [tex]\( 6x - 2 = -4x + 2 \)[/tex]. Let's break down each method step by step:
### Spencer's Approach
Spencer suggests adding [tex]\( 4x \)[/tex] to both sides of the equation:
[tex]\[ 6x - 2 = -4x + 2 \][/tex]
Add [tex]\( 4x \)[/tex] to both sides:
[tex]\[ 6x - 2 + 4x = -4x + 2 + 4x \][/tex]
Simplify the equation:
[tex]\[ 10x - 2 = 2 \][/tex]
Next, add 2 to both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ 10x - 2 + 2 = 2 + 2 \][/tex]
[tex]\[ 10x = 4 \][/tex]
Finally, divide both sides by 10 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{4}{10} \][/tex]
[tex]\[ x = \frac{2}{5} \][/tex]
### Jeremiah's Approach
Jeremiah suggests subtracting [tex]\( 6x \)[/tex] from both sides of the equation:
[tex]\[ 6x - 2 = -4x + 2 \][/tex]
Subtract [tex]\( 6x \)[/tex] from both sides:
[tex]\[ 6x - 2 - 6x = -4x + 2 - 6x \][/tex]
Simplify the equation:
[tex]\[ -2 = -10x + 2 \][/tex]
Next, subtract 2 from both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ -2 - 2 = -10x + 2 - 2 \][/tex]
[tex]\[ -4 = -10x \][/tex]
Finally, divide both sides by -10 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-4}{-10} \][/tex]
[tex]\[ x = \frac{4}{10} \][/tex]
[tex]\[ x = \frac{2}{5} \][/tex]
### Conclusion
Both methods lead to the same solution, [tex]\( x = \frac{2}{5} \)[/tex]. Thus, both Spencer and Jeremiah are correct in their initial steps and their overall approach to solving the equation.
### Spencer's Approach
Spencer suggests adding [tex]\( 4x \)[/tex] to both sides of the equation:
[tex]\[ 6x - 2 = -4x + 2 \][/tex]
Add [tex]\( 4x \)[/tex] to both sides:
[tex]\[ 6x - 2 + 4x = -4x + 2 + 4x \][/tex]
Simplify the equation:
[tex]\[ 10x - 2 = 2 \][/tex]
Next, add 2 to both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ 10x - 2 + 2 = 2 + 2 \][/tex]
[tex]\[ 10x = 4 \][/tex]
Finally, divide both sides by 10 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{4}{10} \][/tex]
[tex]\[ x = \frac{2}{5} \][/tex]
### Jeremiah's Approach
Jeremiah suggests subtracting [tex]\( 6x \)[/tex] from both sides of the equation:
[tex]\[ 6x - 2 = -4x + 2 \][/tex]
Subtract [tex]\( 6x \)[/tex] from both sides:
[tex]\[ 6x - 2 - 6x = -4x + 2 - 6x \][/tex]
Simplify the equation:
[tex]\[ -2 = -10x + 2 \][/tex]
Next, subtract 2 from both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ -2 - 2 = -10x + 2 - 2 \][/tex]
[tex]\[ -4 = -10x \][/tex]
Finally, divide both sides by -10 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-4}{-10} \][/tex]
[tex]\[ x = \frac{4}{10} \][/tex]
[tex]\[ x = \frac{2}{5} \][/tex]
### Conclusion
Both methods lead to the same solution, [tex]\( x = \frac{2}{5} \)[/tex]. Thus, both Spencer and Jeremiah are correct in their initial steps and their overall approach to solving the equation.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.